Determination of childhood and adult attention deficit hyperactivity disorder symptoms in male heroin dependent patients and clinical effects - Öztürk, Halil İbrahim and Yardım Özayhan, Hatice and Etli, Tahsin and Demirel, Başak and Eren, İbrahim (Journal of Dependence, 2023)
Objective: We aimed to determine the frequency and clinical effects of childhood and adulthood attention deficit hyperactivity disorder (ADHD) in male heroin-dependent patients, and to evaluate the clinical conditions that may affect the severity of addiction such as aggression, impulsivity, childhood traumas, anxiety sensitivity, anxiety and depression symptoms. Method: The study was completed with 100 consecutive male volunteers with heroin dependence, who were in the buprenorphine/naloxone stabilization treatment period. Sociodemografic form, Addiction Severtiy Index (ASI), Wender-Utah Rating Scale (WURS), Adult ADHD Self-Report Scale (ASRS), Barratt Impulsiveness Scale, Version 11 (BIS-11), Diagnostic Interview for ADHD in Adults-2.0 Turkish version (DIVA 2.0-Turksih) , Childhood Trauma Questionnare (CTQ) , Buss-Perry Agression Questionnare (BPAQ), Anxiety Sensitivity Index-3 (ASI-3), Medical Outcomes Study Short Form-36 (SF-36) Health Survey Questionnare, Hamilton Depression Rating Scale (HDRS) and Hamilton Anxiety Rating Scale (HARS) were administered to the participants. Results: A history of childhood ADHD was found in 30% and a diagnosis of adult ADHD was found in 14% of the participants who were administered the DIVA 2.0-Turkish. While the non-ADHD group had higher scores in the SF-36 social function and mental health domains (48.21±24.56, 52.15±19.05, respectively), had lower scores in the ASI legal and psychiatric status domains (4.69±1.75, 3.11±1.16, respectively). In the regression analysis, total score of the BPAQ was found to be an important variable that affecting four of the six ASI dimensions (employment/support status, legal status, drug use and psychiatric status). Conclusion: ADHD should be carefully evaluated in heroin-dependent patients. In the treatment of heroin addiction, which is a multidimensional disorder, it would be benefical to specifically address aggression.